Development of Cordyceps javanica BE01 with enhanced virulence against Hyphantria cunea using polyethylene glycol-mediated protoplast transformation - Wang, Wenxiu; Wang, Yahong; Dong, Guangping; Chen, Fengmao (Frontiers in Microbiology, 2022)
Cordyceps javanica has promising application prospects as an entomopathogenic fungus with a wide range of hosts. To enhance the virulence of C. javanica, a polyethylene glycol (PEG)-mediated protoplast genetic transformation system was constructed. Strains overexpressing the subtilisin-like protease genes CJPRB and CJPRB1 and the tripeptidyl peptidase gene CJCLN2-1 were constructed with this system, and the effects of these strains on Hyphantria cunea were tested. The aminoglycoside G418 was used at 800 μg mL-1 to screen the transformants. C. javanica hyphae were degraded with an enzyme mixture to obtain protoplasts at 1.31 х 107 protoplasts mL-1. The transformation of 2 μg of DNA into 1000 protoplasts was achieved with 20% PEG2000, and after 6 h of recovery, the transformation efficiency was 12.33 ± 1.42 transformants μg-1 plasmid. The LT50 values of CJPRB, CJPRB1 and CJCLN2-1-overexpressing C. javanica strains were 1.32-fold, 2.21-fold and 2.14-fold higher than that of the wild-type (WT) strain, respectively. The three overexpression strains showed no significant differences from the WT strain in terms of colony growth, conidial yield and conidial germination rate. However, the infection rate of the CJPRB1 strain was faster than that of the WT strain, with infection occurring within 4-5 days. The CJCLN2-1 strain had a significantly higher mortality rate than the WT strain within 4-10 days after infection. A C. javanica genetic transformation system was successfully constructed for the first time, and an overexpression strain exhibited enhanced virulence to H. cunea compared with the WT strain.